Теоретико-прикладні проблеми відмежування зловживання службовим становищем від перевищення службових повноважень - Музичук, О. М.; Muzychuk, O. M.; Колесник, М. О.; Kolesnyk, M. O. (Наше право. - 2023. - № 1. - С. 162-167, 2023)
Розкрито теоретичні підходи щодо визначення понять «зловживання службовим становищем» та «перевищення повноважень». Проведений аналіз дав змогу запропонувати авторське визначення вказаних категорій. Констатовано, що необхідно розрізняти зловживання владою або службовим становищем та перевищенням влади або службових повноважень. Основні відмінності між цими двома злочинами полягають у: наявності/відсутності додаткових об’єктів злочину, характері об’єктивної сторони, суб’єктах злочинів та наявності/відсутності спеціальної мети злочину. Зауважено, що зловживання владою або службовим становищем вчиняється службовою особою в межах її повноважень, але з метою одержання неправомірної вигоди, тоді як перевищення влади або службових повноважень правоохоронця полягає в тому, що він діє у межах служби, але виходить за межі своїх повноважень та діє незаконними методами. Також відрізняються суб’єкти цих злочинів та наявність/відсутність спеціальної мети злочину.

It is argued that abuse of official position is an illegal act committed by an official during the performance of his official duties, which directly or indirectly harms the state, other persons or society as a whole. Abuse may include the use of an official position to obtain an improper benefit, perform illegal actions, or improperly interfere with the activities of others. Such actions can be relatively minor, such as refusing to provide information, but can also be significant, such as forging documents, demanding an undue advantage, or abusing power to commit criminal acts. It has been established that abuse of power or official authority is the commission of actions by an official that go beyond the powers and competences defined by the norms of the current legislation, and therefore contradict the current legislation. Abuse of power can take many forms, including the use of excessive force, insufficient attention to duty, interference with people’s privacy, or violation of constitutional rights. It was established that it is necessary to distinguish between abuse of power or official position and excess of power or official authority. The main differences between these two crimes are: the presence/absence of additional objects of the crime, the nature of the objective party, the subjects of the crimes and the presence/absence of a special purpose of the crime. It is also worth noting that the abuse of power or official position is committed by an official within the limits of his authority, but with the aim of obtaining an improper benefit, while the excess of power or official authority of a law enforcement officer consists in the fact that he acts within the scope of the service, but exceeds the limits of his authority and acts by illegal methods. The subjects of these crimes and the presence/absence of a special purpose of the crime also differ.

Раскрыты теоретические подходы к определению понятий «злоупотребление служебным положением» и «превышение полномочий». Проведенный анализ позволил предложить авторское определение указанных категорий. Констатировано, что необходимо различать злоупотребление властью или служебным положением и превышением власти или служебных полномочий.
Keywords: державні службовці; державна служба; юридична відповідальність; розмежування; зловживання службовим становищем; перевищення повноважень; civil servants; civil service; legal responsibility; delimitation; abuse of official position; excess of authority; государственные служащие; государственная служба; юридическая ответственность; разграничение; злоупотребление служебным положением; превышение полномочий